2014
DOI: 10.1007/s10072-014-1908-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, case–control study on the effect of pregnancy on seizure frequency in women with epilepsy

Abstract: To evaluate if pregnancy induces a change in seizure frequency and in percentage of subjects remaining seizure-free. This is a prospective case-control study conducted in our tertiary epilepsy centre. Controls were matched 2:1 with the cases for relevant clinical parameters. Cases had to be referred to our centre for at least 9 months before-pregnancy, during pregnancy and the-9-months-after-birth. Controls were followed for the correspondent periods of time: named respectively control period 1-2-3. Seizure fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Most studies report that seizures are stable in over half of WWE during pregnancy, while other studies report that seizure worsening occurs in up to 75% of women during at least one time point during pregnancy. 32,33 The likelihood of seizure worsening depends on several factors: baseline seizure frequency (in the prior month or 9-12 months), seizure types (focal more likely to worsen than generalized-onset seizures), AEDs at beginning of pregnancy (LTG, OXC, polytherapy use are associated with higher risk for seizure worsening), use of therapeutic drug monitoring, and patient adherence.…”
Section: Seizure Control During Pregnancymentioning
confidence: 99%
“…Most studies report that seizures are stable in over half of WWE during pregnancy, while other studies report that seizure worsening occurs in up to 75% of women during at least one time point during pregnancy. 32,33 The likelihood of seizure worsening depends on several factors: baseline seizure frequency (in the prior month or 9-12 months), seizure types (focal more likely to worsen than generalized-onset seizures), AEDs at beginning of pregnancy (LTG, OXC, polytherapy use are associated with higher risk for seizure worsening), use of therapeutic drug monitoring, and patient adherence.…”
Section: Seizure Control During Pregnancymentioning
confidence: 99%
“…Catamenial epilepsy may have its onset in puberty and may occur in the perimenstrual, periovulatory, or luteal phase; the most common form has a perimenstrual pattern, occurring between 3 days before and 3 days after menses. 106 In another study, a higher percentage of women with history of CE remained seizure-free during pregnancy compared to women with noncatamenial epilepsy. 103,112 The molecular pathophysiology of CE remains unclear; perimenstrual CE has been attributed to neurosteroid withdrawal, which is associated with upregulation of extrasynaptic GABA A receptors that mediate tonic inhibition in the dentate gyrus.…”
Section: Neuroprotective Effects Of Estrogensmentioning
confidence: 95%
“…11,[103][104][105][106] Experimental studies indicate that, in general, estrogens have a proconvulsant effect whereas progesterone has anticonvulsant properties. There is clinical evidence that estrogens (and progesterone) may influence the predisposition to epilepsy.…”
Section: Neuroprotective Effects Of Estrogensmentioning
confidence: 99%
“…Seizure outcome in patients with juvenile absence epilepsy is not clear [149], and cognitive deterioration is not rare [150]. A prospective case-control study has shown that pregnancy does not affect seizure frequency in women with epilepsy [151]. Psychogenic nonepileptic seizures are more frequent among women and have possible biological basis [152,153].…”
Section: Epilepsymentioning
confidence: 99%